Comparative Study of Bone Marrow and Blood B Cells in Infantile and Acquired Agammaglobulinemia: POSSIBLE ROLE OF CIRCULATING ANTI-IgM IN PATHOGENESIS - Abdou, Nabih I. (1973)
The status of immunoglobulin (Ig) receptors of the bone marrow dependent (B) cells present in either the bone marrow (BM) or peripheral blood (PB) of three patients with infantile agammaglobulinemia (I-AGG), or seven patients with acquired agammaglobulinemia (A-AGG) is compared with those of 12 controls. Quantitative and qualitative changes of the different classes of Ig receptors on B cells were evaluated by their capacity to bind [(125)I]anti-Ig, to be stained with fluorescinated anti-Ig and their in vitro proliferative capacity upon incubation with the anti-Ig. Patients with I-AGG lacked B cells in both the BM and PB. Whereas BM cells of patients with A-AGG carried receptors similar to control cells, their blood B cells had fewer IgM, IgG, and IgA cells which failed to proliferate in vitro in the presence of the anti-Ig. An anti-IgM of the IgG class was detected in the sera of patients with A-AGG but not in sera of I-AGG. The isolated anti-IgM agglutinated human red cells coated with IgM. The anti-IgM partially blocked the binding of fluorescinated or radiolabeled anti-IgM to IgM peripheral blood lymphocytes of normal controls. The eluted anti-IgM in presence of complement was partially cytotoxic to normal cells. It is concluded that I-AGG-B cell defect is due to failure of B cell development in the bone marrow compartment whereas the peripheral exclusion of IgM cells by an anti-IgM with the subsequent failure of differentiation of both IgG and IgA cells could be an important mechanism in A-AGG-B cell defect.